Rethinking Automation and the Future of Work with Hannah Arendt - Rosalie A. Waelen (Journal of Business Ethics, 2025)
Recent technological developments have given rise to debates about automation and the future of work. These debates touch on concerns about the availability, nature, and meaningfulness of jobs in the present and near future. The aim of this article is to show that Hannah Arendt's phenomenology of labor, work, and action can improve current debates about automation and the future of work. First of all, an analysis of Arendt's critique of modern society and the more recent notion of 'immaterial labor' demonstrates that we (still) live in a society dominated by labor and consumption. Second, a conceptual distinction between labor, work, and action can add relevant nuances to contemporary debates about automation and the future of work. Third, Arendt's warning for a society of laborers without labor inspires to add over-consumption to the list of problems arising from automation. Fourth, Arendt's description of the human condition can give clarity to contemporary worries about automation's impact on meaning. It is concluded, finally, that a revaluation of work and action can counter the threats associated with the automation of labor.
Keywords: 300; Hannah Arendt; The Human Condition; Practical Philosophy; AI Ethics; The Future of Work; Automation; Labor